Design and Testing of a Novel Slot Retractor for Neonatal Frenotomy. Issue 4 (October 2016) - Rahman, Tariq; Tran, Nghia N.; Jani, Gita; Udenze-Utah, Chinedum N.; Siddiqui, Shehla S.; Golub, Leonard M.; Restrepo-Ormsby, Adriana; Shaffer, Thomas H.
Abstract : A new slot retractor for frenotomy has been developed that offers a unique design that will lead to fewer complications and allow primary care physicians (neonatologists, pediatricians, family physicians) to perform frenotomy in the nursery or office. The novel 3-dimensional printed retractor has side walls for better tissue protection, a built-in slot, and an ergonomic handle. An efficacy and safety study was conducted with 43 infants with the newly designed slot retractor. Results showed that there were no partial divisions at discharge; all babies were able to breastfeed almost immediately after frenotomy and continued to breastfeed until hospital discharge, and there were no adverse events.